An Approach to Quickly Establish Regional Carbon Management System - Zhu, Chaoyong; Gao, Peidao; Zhang, Yang; Chen, Bo (Frontiers in Energy Research, 2022)
Local governments are the main actors in achieving carbon peaking and carbon neutrality goals. The existing carbon management system is mainly for the country, industry or enterprise, and there is no carbon management design method for local governments. Therefore, from the perspective of local governments, a regional carbon management approach based on carbon-electricity intensity and carbon efficiency is proposed. First, based on electricity consumption data, combined with regional industry energy statistics, a carbon-electricity intensity indicator is established to estimate the carbon emissions of enterprises, and then different carbon emission reduction strategies are constructed using carbon efficiency indicator. This study proposes two types of emission reduction strategies, marginal opt-out and collective action, and conducts scenario simulation analysis using a case study from a city in southeastern China. The baseline scenario shows that although the marginal opt-out strategy has the lowest economic cost, the emission reduction rate is also lower, while the collective action strategy can achieve the emission reduction target faster, but only at a higher economic cost. This approach is suitable for the construction of the initial carbon management system in areas dominated by electricity consumption, taking into account the two dimensions of economy and environment, and can be applied to various decision-making scenarios, which is beneficial for local governments to quickly start the carbon management system.